2014
DOI: 10.1039/c3ce42286k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical analysis of lp⋯π intermolecular interactions in derivatives of 1,2,4-triazoles

Abstract: The calculations performed on the evaluation of the electrostatic potential provide deeper insights into the nature of lp⋯π interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 92 publications
4
31
0
Order By: Relevance
“…In the presence of a strong acceptor and donor atom, the crystal packing will be predominantly controlled by the presence of strong hydrogen bonds such as O/N-H· · · O/N. 4 In the past decade, the focus has shifted from strong intermolecular interactions to weak intermolecular interactions such as C-H· · · O/N, [5][6][7][8] C-H· · · X (X = -F, -Cl, -Br, -I), [9][10][11][12][13][14] C-H· · · π 15 and π · · · π 16,17 and lp · · · π 18,19 interactions present in the crystal structures. Weak * For correspondence intermolecular interactions involving organic fluorine have received special attention due to its small size, electronegativity and lipophilic character.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a strong acceptor and donor atom, the crystal packing will be predominantly controlled by the presence of strong hydrogen bonds such as O/N-H· · · O/N. 4 In the past decade, the focus has shifted from strong intermolecular interactions to weak intermolecular interactions such as C-H· · · O/N, [5][6][7][8] C-H· · · X (X = -F, -Cl, -Br, -I), [9][10][11][12][13][14] C-H· · · π 15 and π · · · π 16,17 and lp · · · π 18,19 interactions present in the crystal structures. Weak * For correspondence intermolecular interactions involving organic fluorine have received special attention due to its small size, electronegativity and lipophilic character.…”
Section: Introductionmentioning
confidence: 99%
“…The study of intermolecular interactions has become prominent in crystal structure analyses in the last decade [17][18][19][20][21][22][23][24]. Hirshfeld surface analysis is a characteristic method to visualize and characterize the intermolecular interactions of molecular crystals.…”
Section: Single-crystal X-ray Structuresmentioning
confidence: 99%
“…It has been shown that lp-p interactions play a significant role in crystal packing of 1,2,4-triazoles and that their energies are in the range 16-50 kJ mol À1 [24]. The calculated energy results for 5 agreed with these values and it can be concluded that the strengths of lp-p interactions largely depend on the availability of the electrons of the corresponding electron-rich atoms, the nature of the functional group as well as the distance from the electron-deficient ring.…”
Section: Crystal Structures Of 5 Andmentioning
confidence: 99%
“…Interactions that involve aromatic rings include p-p stacking, CH-p, and cation-p interactions [18]. The lp-p stacking interactions involve an electrondeficient aromatic ring and a lone pair of neutral electronrich molecules, which have been thoroughly studied both theoretically and experimentally [19][20][21][22][23][24][25][26]. The lp-p stacking interactions involve an electrondeficient aromatic ring and a lone pair of neutral electronrich molecules, which have been thoroughly studied both theoretically and experimentally [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation